The Efficacy of Teaching Campus Program in Promoting Primary School Students’ Literacy Skills - Tri Wintolo Apoko; Samuel Pratama; Josua Simatupang; Amara Febita; Andiko Pratama (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study aims to unveil students’ perceptions of TCP in promoting their literacy skills and to examine the correlations between their perceived TCP and the test scores as well as its contribution to their literacy skills. The participants were 20 students of the fifth grade at one state primary school in Jakarta. With a sequential explanatory mixed-methods design, this study combined quantitative analyses of a questionnaire and test scores—using descriptive statistics to find out perceptions of the programimprovement in literacy skills, motivation and confidence, and effectiveness of facilitation and collaboration, a bivariate correlation analysis to assess the relationships with the test scores, and t-test analysis to compare the mean from two data groups—with qualitative responses from semi-structured interviews which were analyzed through thematic analysis. The results showed that TCP had strong positive impact, covering students’ improvement in literacy skills, the motivation and their confidence, and facilitation and collaboration. However, no significant corelations were found among the perceived efficacy and test scores even though the paired samples t-test results demonstrated a statistically significant increase in students' literacy skills in the TCP.